An improved theory in the determination of aerodynamic damping for a horizontal axis wind turbine (HAWT). Issue 213 (June 2021) - Chen, Yisu; Wu, Di; Yu, Yuguo; Gao, Wei
Abstract: The aerodynamic damping reflects the aero-structure interaction and is intrinsically involved in a fully coupled turbine. However, it is still of great importance to theoretically quantify the aerodynamic damping of a HAWT in some cases. The existing theory can reasonably characterize the aerodynamic damping level of a HAWT with rigid blades, minute shaft tilt and yaw angles, while certain discrepancies were observed when compared with either experimental or numerical damping results of a more realistic turbine. This study aims to provide an improved theory to incorporate more realistic conditions (i.e., blade flexibility, shaft tilt and yaw angle) in aerodynamic damping estimation. Good agreements are found between the proposed theory and numerical results with varied influential factors, upon which modification factors against the original theory are created and discussed. Finally, the aerodynamic damping of tower is determined and included in a decoupled fatigue analysis framework to demonstrate the potential application of this improved aerodynamic damping theory. Highlights: An aerodynamic damping theory including blade flexibility, shaft tilt, yaw angle and tower shape effects is developed. Qualitative trend of aerodynamic damping related with influential factors is determined. Quantitative range of related factors within which the aerodynamic damping is highly affected. A potential application of the improved theory in wind turbine dynamic analysis is depicted.